Midwives’ Knowledge and Attitude about Antenatal Care in Rumbai Sub-district - Muhammad Lingga Primananda; Noviardi Noviardi (Indonesian Journal of Obstetrics and Gynecology, 2026)
AbstractObjective: To determine the relationship between the levels of knowledge and attitudes of midwives in the Rumbai sub district and the implementation of 10T antenatal care. Methods: This was a cross-sectional study with an analytic observational design involving 43 midwives in the Rumbai sub district. Data were collected using a questionnaire that had undergone validity and reliability testing using the SPSS program. The implementation of 10T antenatal care was assessed using a Likert scale. Data were analyzed using SPSS version 23.0. Results: The majority of respondents were aged 31–35 years (39.5%), had a diploma (D3) as their highest educational level (55.8%), had 1–5 years of work experience (46.5%), and worked in clinics (44.2%). There were significant relationships between educational level (p=0.031, C=0.294), knowledge level (p=0.029, C=0.211), years of service (p=0.026, C=0.094), and attitudes(p=0.048, OR=1.391) of midwives and the implementation of 10T antenatal care in the Rumbai sub-district. Conclusion: This study demonstrated a significant relationship between midwives’ attitudes and the implementation of 10T antenatal care in the Rumbai sub-district. Additionally, there were associations between educational level, knowledge level, and the implementation of 10T antenatal care. Among the respondents, 88.3% (20 out of 24) of midwives with a diploma (D3), 77.8% (14 out of 18) with a bachelor’s degree, and 0% (0 out of 1) with a master’s degree completed the 10T implementation. These findings indicate that midwives with a diploma (D3) demonstrated the highest level of implementation compared to those with higher educational levels. Therefore, efforts to improve the implementation of 10T antenatal care should be tailored according to the educational background of midwives. Keywords: antenatal care, attitude, level of knowledge, midwives